2007
DOI: 10.5194/angeo-25-1669-2007
|View full text |Cite
|
Sign up to set email alerts
|

Motion of flux transfer events: a test of the Cooling model

Abstract: Abstract. The simple model of reconnected field line motion developed by Cooling et al. (2001) has been used in several recent case studies to explain the motion of flux transfer events across the magnetopause. We examine 213 FTEs observed by all four Cluster spacecraft under a variety of IMF conditions between November 2002 and June 2003, when the spacecraft tetrahedron separation was ∼5000 km. Observed velocities were calculated from multi-spacecraft timing analysis, and compared with the velocities predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 65 publications
7
73
0
Order By: Relevance
“…Observations at scales between 100 and 5000 km have enabled the study of FTE motion at the magnetopause (Owen et al, 2001;Wild et al, 2005a;Dunlop et al, 2005;Fear et al, 2005Fear et al, , 2007, FTE structure (Hasegawa et al, 2006;Owen et al, 2008), further study of the statistics of FTE occurrence (Wang et al, , 2006Fear et al, 2005Fear et al, , 2007 and conjugated magnetopause/ionospheric studies using the SuperDARN radar network (Wild et al, 2001(Wild et al, , 2003(Wild et al, , 2005b(Wild et al, , 2007Marchaudon et al, 2004;Amm et al, 2005). In this paper we present the first observations of FTEs from the Cluster 10 000 km separation magnetopause crossing season, enabling in situ examination of the scale lengths of an FTE in all three dimensions.…”
Section: Have Beenmentioning
confidence: 99%
See 3 more Smart Citations
“…Observations at scales between 100 and 5000 km have enabled the study of FTE motion at the magnetopause (Owen et al, 2001;Wild et al, 2005a;Dunlop et al, 2005;Fear et al, 2005Fear et al, , 2007, FTE structure (Hasegawa et al, 2006;Owen et al, 2008), further study of the statistics of FTE occurrence (Wang et al, , 2006Fear et al, 2005Fear et al, , 2007 and conjugated magnetopause/ionospheric studies using the SuperDARN radar network (Wild et al, 2001(Wild et al, , 2003(Wild et al, , 2005b(Wild et al, , 2007Marchaudon et al, 2004;Amm et al, 2005). In this paper we present the first observations of FTEs from the Cluster 10 000 km separation magnetopause crossing season, enabling in situ examination of the scale lengths of an FTE in all three dimensions.…”
Section: Have Beenmentioning
confidence: 99%
“…This was done by finding the time delay which maximised the cross-correlation between each pair of B N time series, and then adjusting the lag by eye if necessary to achieve the best alignment of three key points: the midpoint of the bipolar B N signature and the positive and negative peaks. These time differences are given in Table 1, along with the uncertainties on each timing measurement, within which all three key points are aligned, as described by Fear et al (2007). Using the procedure described by Harvey (1998, p. 311), the velocity of the FTE at 19:33 UT was found to be (399, 97, 16) LMN km s −1 , and the velocity of the .…”
Section: Fte Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…Here we report a comprehensive survey of the MESSENGER magnetic field data for the occurrence of FTEs. From definitions developed for Earth's magnetosphere [e.g., Wang et al, 2005;Fear et al, 2007], six FTEs were identified during the two flybys with all, save one, strongly resembling flux ropes. Unfortunately, MESSENGER does not make the high-time-resolution plasma moment measurements necessary to analyze these FTEs using the Grad-Shafranov (GS) reconstruction technique [Zhang et al, 2008;Eriksson et al, 2009].…”
Section: Introductionmentioning
confidence: 99%